The self-build experience : institutionalisation, place-making and city building - Salet, W. G. M.; D'Ottaviano, Camila; Majoor, Stan; Bossuyt, Daniel (Urban policy, planning and the built environment., 2020)
Using a broad international comparative perspective spanning multiple countries across South America, Europe and Africa, contributors explore resident-led self-building for low- and middle-income groups in urban areas. Although social, economic and urban prosperity differs across these contexts, there exists a recurring, cross-continental, tension between formal governance and self-regulation. Contributors examine the multifaceted regulation dilemmas of self-building under the conditions of modernisation and consider alternative methods of institutionalisation, place-making and urban design, reconceptualising the moral and managerial ownership of the city. Innovative in scope, this book provides an array of globalised solutions for navigating regulatory tensions in order to optimise sustainable development for the future.